Association of waist-to-height ratio with all-cause and obesity-related mortality in adults: a prospective cohort study - Wang, Gang; Luo, Yunpeng; Yang, Tianyi; Huang, Jukai; Li, Jiaoyue; Liu, Yan; Yang, Xiaohui (Frontiers in Nutrition, 2025)
BackgroundThe waist-to-height ratio (WHtR) is the optimal indicator for assessing obesity-related diseases. Establishing a unified standard for investigating the relationship between WHtR and mortality is an urgent need.MethodsThis cohort study included 47,741 U. S. adults from the National Health and Nutrition Examination Survey database from 1999 to 2018. The survival outcomes were all-cause mortality and obesity-related mortality. The associations between WHtR and mortality were quantified using restricted cubic splines and Cox proportional hazards regression models.ResultsAmong the 47,741 participants, the association between WHtR and all-cause mortality was characterized by a distinct U-shaped curve, with an inflection point at 0.58. The relative risk was minimized in the Q3 category, with a hazard ratio of 0.753 (95% CI, 0.752–0.754). WHtR demonstrated a J-shaped nonlinear relationship with the risk of mortality from cardiovascular disease, cancer, and diabetes (p < 0.001), with an inflection point of 0.58 for each condition. A higher WHtR (≥0.58) was associated with increased risks of mortality from cardiovascular disease (35.5%), cancer (4.5%), cerebrovascular disease (10.0%), and diabetes (69.8%). In subgroup analyses, the cutoff value of 0.58 for WHtR showed good stability across different populations.ConclusionWe found that the WHtR is associated with all-cause mortality in a U-shaped manner and provides a relatively stable cutoff value (0.58) for mortality related to obesity-associated diseases. This finding offers a convenient anthropometric indicator for body management in the general population.